Жанрові стратегії в романі Б. Ачаги «Сім будинків у Франції» - Касьян, Катерина; Kasian, Kateryna (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті на матеріалі роману баскського письменника Бернардо Ачаги «Сім будинків у Франції» зроблено спробу виявити та проаналізувати жанрові стратегії, що їх використав автор, та особливості їхнього функціо-нування в дискурсі постмодерну./ Creative work of Basque writer exerts great influence over genre canon of Basque literature. Genre aspect of his works is of the most interest for our investigation. Compositional, structural, genre experiments of the author make it possible to exceed the scope of the interpretation within the framework of double code strategy. Colonial problematic is developed by means of narrative conventions of colonial novel. Key point of the colonial genre’s ontology is interrelations between center and periphery, demonstrated by B. Atxaga. A break with traditional narrative and traditional colonial novel is quite logical from the point of view of postmodern aesthetic. Deconstruction of genre conventions of colonial novels is aimed at challenging the ideas of Eurocentrism and imperialism as the basis of vision of civilizational mission of European culture in the colonies.
Genre Strategies in the Novel by B. Atxaga “Seven Houses in France”
Касьян К. Жанрові стратегії в романі Б. Ачаги «Сім будинків у Франції» / Катерина Касьян // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 50-54.
Keywords: колоніальний роман; жанрова модель; комедія інтриги; реконструкція; гетеропія; colonial novel; genre model; comedy of intrigue; deconstruction; heterotopy